Effectiveness of Sambas Language Health Promotion Video on Food Hygiene Sanitation at KWT Rose in Tambatan Village - Salsa Septiani Nur; Linda Suwarni; Selviana Selviana (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Food sanitation hygiene is the process of minimizing food contamination from various sources to control risk factors for food contamination that could potentially cause health problems. Video media can stimulate two senses, namely the eyes and ears, which makes understanding clearer for the audience. This research aims to improve the knowledge and attitude of Rose Women Farmers Group (KWT) regarding Food Hygiene Sanitation in Tambatan Village, Sambas Regency. Methods: Pre-Experiment design with one group pre-test and post-test approach was used in this study. It was conducted in Tambatan Village, Teluk Keramat Sub-district, Sambas Regency from September to December 2024. The research sample of 30 respondents was determined through total sampling technique. The research instrument used a specially designed questionnaire to collect data on food sanitation hygiene. Data were analyzed using univariate and bivariate analysis using Wilcoxon test. Results: The Wilcoxon test showed a difference in the mean knowledge and attitude scores between before and after the sambas language video media intervention was given. The mean knowledge score increased from 5.03 to 9.43 (p-value = 0.000 < 0.05) and the mean attitude score increased from 38.57 to 47.33 (p-value = 0.000 < 0.05). Conclusion: It can be concluded that health promotion using sambas language videos is proven effective in improving KWT Rose's knowledge and attitude regarding food sanitation hygiene.